Domestic macroeconomic adjustment to oil price shocks under different exchange rate regimes in Malaysia - Chong, Hui Ing (2007)
This thesis examines on the insulation properties of flexible exchange rate regime against fixed exchange rate regime from oil price shocks. A monthly sample 1980-2005 from Malaysia is investigated whether the response of output, exchange rate and price level to oil price shocks are different across exchange rate regimes in the short run by applying Structural Vector Autoregressive model. The oil prices are found to be exogenous to the macroeconomic variables in Malaysia. Results show that the short run output responses to oil price disturbances are smoother under flexible exchange regime than fixed exchange regime. And there is asymmetric response of domestic variables to positive and negative oil price shocks across and within exchange regimes.